FSTM UPM Strengthens Food Security Awareness through Open Day @FoodTech 2025 - Universiti Putra Malaysia, Pejabat Strategi Korporat dan Komunikasi (Pusat Strategi Dan Perhubungan Korporat, Universiti Putra Malaysia, 2025)
SERDANG, October 15 – The Faculty of Food Science and Technology (FSTM), Universiti Putra Malaysia (UPM) strengthened its role in raising public awareness on the importance of food security through the organisation of Open Day @FoodTech UPM 2025, themed “Transforming Our Plates, Strengthening Food Security.”